Pengaruh Harga, Promosi, dan Kualitas Produk terhadap Omzet Penjualan pada UD Arida Tirta Jaya (FF Tirta) Jakarta Timur - Ari Wahyu Leksono; Adhis Darussalam Pamungkas; Hugo Aries Suprapto; Vella Anggresta (Neolectura, 2022)
The purpose of this study was to determine the effect of price, promotion, and product q The purpose of this study is to determine the influence of prices, promotion, and product quality on sales turnover on UD. Arida Tirta Jaya (FF Tirta) East Jakarta. This study uses multiple linear regression analysis methods for the data processing process. The population and sample in this study are all workers who work in UD. Arida Tirta Jaya (FF Tirta) East Jakarta, and totaling 30. Data collection methods using a questionnaire. Sampling techniques using saturated samplel techniques. The data collection technique used by researchers is a questionnaire. The data analysis technique used is the classical assumption test, multiple linear regression test, and statistical test. The results of this study that for price variables (X1), and promotion (X2) there is an insignificant influence on sales turnover, while for product quality variables (X3) has a very significant effect on sales turnover. uality on sales turnover at UD. Arida Tirta Jaya (FF Tirta) East Jakarta. This research is a descriptive type of research. The population and research sample in this study were all UD employees. Arida Tirta Jaya (FF Tirta) East Jakarta, totaling 30 employees. Methods of data collection using a questionnaire. The sampling technique used was the saturated sample technique. The data collection technique used by the researcher is a questionnaire. The data analysis technique used was the classical assumption test, multiple linear regression, and statistical tests. The results showed that the multiple linear regression value was Y = 22.675 + 0.068 (X1) + 0.0341 (X2) + -0.272 + e, meaning that the constant value was positive (22.675), indicating a positive influence on the independent variables (price, promotion, and product quality). If the independent variable increases or has an effect, it will increase the dependent variable (sales turnover variable). The results of the F test are identified with a Sig value of 0.049 <0.05 so it can be concluded that there is a simultaneous effect of price, promotion, and product quality on sales turnover at UD. Arida Tirta Jaya (FF Tirta).